Prospects for Markets for Internationally Transferred Mitigation Outcomes under the Paris Agreement - Strand, Jon (World Bank, Washington, DC, 2022)
The Paris Agreement provides for parties to use internationally transferred mitigation outcomes in implementing their Nationally Determined Contributions. This paper analyzes forward trading of these outcomes in the presence of two forms of uncertainty: (1) uncertainty about the fulfillment of Nationally Determined Contribution targets, and (2) uncertainty about the existence and functioning of the forward, options, and future spot markets markets for internationally transferred mitigation outcomes. When parties can sell and buy internationally transferred mitigation outcomes forward, access to call options for late purchases leads to correspondingly larger forward sales, or less current mitigation. Access to put options for late internationally transferred mitigation outcome sales does not affect forward trading outcomes but increases late sales for net sellers. Access to options markets is welfare enhancing for all parties, and call options help parties stay in compliance with their Nationally Determined Contributions at the Paris Agreement end point, 2030. The existence of internationally transferred mitigation outcome markets may be in peril, however, as banking beyond 2030 is not allowed. The availability and functioning of internationally transferred mitigation outcome markets can be enabled or improved by increased climate finance provided by donors. With no options markets, host countries will still sell internationally transferred mitigation outcomes forward, albeit less so, and rely on access to more expensive “backstop” mitigation for ex-post compliance with their Nationally Determined Contributions. Closed-form solutions are derived for trading and its welfare impacts in all the option contract alternatives, given that parties’ uncertainties about fulfilling their commitments are uniformly distributed. The welfare impact of the availability of put and call option contracts is then strongly increasing in uncertainty, and in ex-post and forward outcome prices.